2017
DOI: 10.1007/s00198-017-4326-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a two-step population-based osteoporosis screening program using FRAX: the randomized Risk-stratified Osteoporosis Strategy Evaluation (ROSE) study

Abstract: Compared to an office-based case-finding strategy, the two-step systematic screening strategy had no overall effect on fracture incidence. The two-step strategy seemed, however, to be beneficial in the group of women who were identified by FRAX as moderate- or high-risk patients and complied with DXA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
1
14

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 28 publications
5
80
1
14
Order By: Relevance
“…The current findings were in line with the primary findings of the two previous randomized pragmatic screening trials for fracture prevention, the ROSE study and the SCOOP study. In the ROSE study (Denmark) that studied women aged 65 to 80 years, screening also did not statistically significantly reduce the incidence of the main outcome major osteoporotic fractures (HR = 0.91; 95% CI 0.83–1.01) . Furthermore, in the SCOOP study (UK), performed among women aged 70 to 85 years, screening did not statistically significantly reduce the incidence of the main outcome osteoporotic fractures (HR = 0.94; 95% CI 0.85–1.03) .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The current findings were in line with the primary findings of the two previous randomized pragmatic screening trials for fracture prevention, the ROSE study and the SCOOP study. In the ROSE study (Denmark) that studied women aged 65 to 80 years, screening also did not statistically significantly reduce the incidence of the main outcome major osteoporotic fractures (HR = 0.91; 95% CI 0.83–1.01) . Furthermore, in the SCOOP study (UK), performed among women aged 70 to 85 years, screening did not statistically significantly reduce the incidence of the main outcome osteoporotic fractures (HR = 0.94; 95% CI 0.85–1.03) .…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, in the ROSE and the SCOOP studies, a clinically relevant effect on these primary outcomes cannot be excluded. Importantly, in both the ROSE and SCOOP studies, a statistically significant reduction in hip fractures was observed, but we have some concerns about these significant secondary results of both the ROSE and SCOOP studies.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although a 2% cut‐off for FREM would result in a large number of false‐positives, this would be acceptable in practice, as the next step would be more detailed screening (ie, by DXA scanning) and only possible treatment after that. As population‐based screening for osteoporosis has been suggested in Denmark, a screening program of only those with a FREM value above 2% would be feasible because it is a much smaller scale than a population screening . The most commonly used intervention threshold based on FRAX in a range of national guidelines is a 10‐year MOF risk of 20%, though the threshold is as low as 4% in some areas of the world .…”
Section: Discussionmentioning
confidence: 99%